First Report of Citrus variegation virus in Palestine Sweet Lime, as Coffee Shade in Costa Rica - Moreira Carmona, Lisela (2011)
Symptoms resembling those of Citrus variegation virus (CVV) were observed in old Palestine sweet lime trees (Citrus limettioides Tan.) used as coffee shade in the Central Valley in Costa Rica. The symptoms include leaf flecking, mosaic, malformation, and dwarfing. This disease was transmitted by grafting to “Valencia” sweet orange (C. sinensis L.), Etrog Citron (C. medica L.), and sweet lime under greenhouse conditions. Symptoms were severe in Palestine sweet lime all year long, but sweet orange and Etrog citron were asymptomatic under high temperature. Reverse transcription polymerase chain reaction (RT-PCR) was used to confirm the presence of CVV in young leaves from sweet lime trees collected from field, and other Citrus spp. grafted and maintained in the greenhouse at University of Costa Rica. Fresh tissue from trees infected with CVV obtained from the USDA (Riverside, California), was used as positive control. Furthermore, the sequence obtained (605 bp) was analyzed by Blastn algorithm which showed 97% homology with CVV RNA 3 (GenBank Accession No. AF434912). Additionally, small scale virus purification was carried out and isometric particles (26 to 32 nm) were observed under the electron microscope. To our knowledge, this is the first report of the presence of CVV in Costa Rica infecting Palestine sweet limes. Also, we remark on the potential of Palestine sweet lime as a host plant indicator in biological indexing of CVV